La femme et le sacrifice : d'Antigone à la femme d'à côté - Dufourmantelle, Anne (Denoël, 2007)
On a sacrifié les femmes au nom d'à peu près tout : morale, religion, politique, amour, maternité... Aujourd'hui encore, malgré les discours d'émancipation, persistent viols, harcèlements, sévices conjugaux, interdits et humiliations. Le destin de la féminité en Occident serait-il sacrificiel? En témoignent ces grandes héroïnes qui foisonnent dans nos mythes, nos légendes d'amour, nos religions, les textes fondateurs de notre culture, toutes plus fascinantes les unes que les autres. Elles ont pour nom Iphigénie, Hélène, Penthésilée, Médé, Iseut ou Jeanne d'Arc mais elles sont aussi des sœurs, des voisines, des exilées, des femmes croisées tous les jours dans la rue, prises à leur insu dans des vies manquées, blanches... De quel sacrifice ignoré la vie de ces femmes se soutient-elle? De quelle façon ces figures mythiques circulent-elles dans notre inconscient? Dans un essai de mythologie quotidienne, Anne Dufourmantelle interroge et retourne les destins spectaculaires de ces héroïnes en les confrontant à ceux, anonymes, parfois tragiques, de ces proches inconnues. D'une écriture subtile, elle approche la secrète texture de nos névroses et déploie la dramaturgie, aussi énigmatique que salvatrice, d'une véritable érotique du sacrifice au féminin.
Donné en lecture: p.9-12
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; inégalités; mythologie; philosophie; premier cycle; psychanalyse; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; violences contre les femmes*

Contract and domination - Pateman, Carole; Mills, Charles W. (Polity, 2007)
« Contract and Domination offers a bold challenge to contemporary contract theory, arguing that it should either be fundamentally rethought or abandoned altogether. Since the publication of John Rawls's A Theory of Justice, contract theory has once again become central to the Western political tradition. But gender justice is neglected and racial justice almost completely ignored. Carole Pateman's and Charles Mills's earlier books, The Sexual Contract (1988) and The Racial Contract (1997), offered devastating critiques of gender and racial domination and the contemporary contract tradition's silence on them. Both books have become classics of revisionist radical democratic political theory. Now Pateman and Mills are collaborating for the first time in an interdisciplinary volume, drawing on their insights from political science and philosophy. They are building on but going beyond their earlier work to bring the sexual and racial contracts together. In Contract and Domination, Pateman and Mills discuss their differences about contract theory and whether it has a useful future; excavate the (white) settler contract that created new civil societies in North America and Australia; argue via a "non-ideal" contract for reparations to black Americans; confront the evasions of contemporary contract theorists; explore the intersections of gender and race and the global sexual-racial contract; and reply to their critics. »–Page 4 de la couverture.
Section: ix, 306 pages ; 24 cm.
Keywords: approches et analyses; capitalisme; com5170; contrat social; cours; discipline; histoire et politique; intersectionnalité; patriarcat; philosophie; philosophie politique; pol4212; premier cycle; racisme; rapports de domination; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires